An observational study to assess the Helicobacter pylori infection rates in patients with cholelithiasis - Kankaria, Jeevan; Madagond, Santosh; Bhat, Akshita (International Surgery Journal, 2023)
Background: Cholelithiasis and chronic cholecystitis cholelithiasis is fairly common all around the world. Since chronic inflammation causes repeated trauma to the gallbladder mucosa and DNA damage led by high or abnormal bile acid exposure, gallstones are closely related to the development of hepatobiliary cancers. After cholecystectomy, some patients experience ongoing upper abdomen pain, which is distressing for the surgeons and raises the possibility of a concomitant upper gastrointestinal issue, which in most cases turned out to be peptic ulcer disease. Numerous studies have found various Helicobacter species in the gallbladder tissue, gallstones, and bile taken from the gallbladder. We conducted this study to assess the relationship between cholelithiasis and H. pylori infection in the stomach. Ascending infection of H. pylori from the stomach and duodenum to biliary tree may have function in development of gall stone production and hepatobiliary carcinomas. Methods: Hospital based cross sectional observational study on patients admitted in surgical wards of SMS Hospital Jaipur for laparoscopic cholecystectomy. All patients underwent UGI and gastric antral biopsy followed by laparoscopic cholecystectomy, gastric mucosa and GB mucosa were subjected to Warthin starry silver stain for detection of H. pylori. Results: Out of 116 patients who underwent upper GI endoscopy followed by laparoscopic cholecystectomy, 29 (25%) patients were positive for H. pylori infection. Conclusions: This study shows significant positive co-relation between H. pylori infection in stomach, gall bladder to chronic cholecystitis and cholelithiasis, which signifies gastric colonisation of H. pylori has it’s role in biliary pathologies through ascending infection, the effectiveness of H. pylori eradication therapy in preventing these pathologies need to be studied further.